Lysosomal responses to different gold forms (nanoparticles, aqueous, bulk) in mussel digestive cells: a trade-off between the toxicity of the capping agent and form, size and exposure concentration. Issue 5 (28th May 2017) - Jimeno-Romero, A.; Izagirre, U.; Gilliland, D.; Warley, A.; Cajaraville, M. P.; Marigómez, I.; Soto, M.
Abstract: Gold nanoparticles (NPs) are increasingly used in technological materials and consumer products and may have toxicological characteristics distinct from bulk and aqueous gold. The aim of this work was to understand the effects of Au NPs especially, how the form, the size and the coating influence bioaccumulation/biodistribution and toxicity of NPs in mussels, Mytilus galloprovincialis . Mussels were exposed for 3 d to concentrations of Au (0.75, 75 and 750 μg Au/l) supplied as Au-Cit NPs (5 and 40 nm; Au5-Cit and Au40-Cit), bulk and aqueous Au (HAu(III)Cl4 ), and to the capping agent (Na-citrate) in doses used in the formulation of NPs (0.005, 0.5, 5 mg/l). Citrate-stabilised NPs formed stable suspensions of aggregates in seawater (SW) available for mussels. Au accumulation in soft tissues was similar in Au40-Cit and aqueous Au exposed mussels, lower in Au5-Cit and negligible after bulk exposure. Au NPs were identified (X-ray microanalysis) in different compartments of the endolysosomal system in digestive cells, and small size NPs (5 nm) were more accumulated than 40 nm NPs, aqueous and bulk. The degree of lysosomal membrane destabilisation was related with intralysosomal metal accumulation and depended on the form, NP size (Au5-Cit > Au40-Cit > aqueous > bulk) and concentration. Citrate alone provoked extreme reduction in lysosomal membrane stability. Toxicopathic alterations were recorded in digestive gland cells (vacuolisation, swollen RER, connective tissue disruption and cell death) especially in mussels exposed to 40 nm NPs. Deleterious effects resulted from digestive tract obliteration (agglomerates) and digestion malfunction. The toxic effect of Au-Cit NPs was influenced both by NP size, capping agent composition and the dose of capping agent carried by NPs, which was size dependent.